Mulheres silenciadas: vivências de viuvez nos anos de chumbo (1970-1980) - Ribeiro, Claudia Caroline Robles [UNESP] (2015)
This research aims to understand cultural practices and representations of the female widowhood and widowhood as institutionalized compulsory in the period of the Brazilian dictatorship in the years 1970 to 1980 breaks with the standards established socially. From the construction of female education and pre-stipulated models for the standards required socalled family girls, we analyze how women's social roles influenced the construction of stereotypical representations of female widowhood. This is to resume the marital status given as national as well as the assigned values that reinforce stereotypes that obscure the participation of widows as social actors, relegating them to the grumbling and uncomfortable representations, what remained invisible as research subjects. From the perspective of Cultural History, the research is based on empirical analysis of a reality through oral histories of women in the State of São Paulo (officially married or not) who have disparate experiences at the loss of their husbands / partners by intervention of the enforcement agencies. Search also analyze information that were not properly analyzed by the historiography taking as initial premise the redefinition of widowhood, oral reports and analysis from multiple sources to consider the different experiences of widows who, reviewing traditional roles, built new identities turning into subjects power and protagonists in history. From the different experiences we seek to changes in the rituals of death and the influence these have in maintaining the memory of their husbands / partners. We start with the construction of a woman from childhood through youth and focusing on adulthood to understand how these women conceived his life from the marriage and how death was breaking project plans and a family life. As official militant leftist organizations or not, these women experienced situations that limits their daily fractured and changed their IDs so...